Design of Emergency Response System to Minimize Incident Impacts: Case Study for Maryland District 7 Network. Issue 1 (January 2014) - Kim, Hyeonmi; Kim, Woon; Chang, Gang-Len; Rochon, Steve M.
Analysis of incident data from the Maryland Highway Administration leads to the conclusion that efficient operations of an incident management team can contribute to reduction in not only response time but also clearance time. This paper presents an integer programming model for optimizing the deployment locations of emergency response units. Unlike models in most existing studies, the proposed model is designed to assign the available units to minimize the total delay caused by incidents rather than to minimize the units' average response times. By giving more weight to locations likely to have more severe incidents and accounting for the variance in incident duration, the proposed model with incident data from Maryland can outperform both the popular P-median model and state-of-the-practice deployment strategies. Extensive sensitivity analyses with respect to various traffic volumes and incident frequencies have also confirmed the superior performance of the proposed model in minimizing the total delay caused by incidents.